God and the green divide: religious environmentalism in black and white - Baugh, Amanda J. (University of California Press, 2017)
"American environmentalism historically has been associated with the interests of white elites. Yet religious leaders in the twenty-first century have helped instill concern about the earth among groups diverse in religion, race, ethnicity, and class. How did that happen and what are the implications? Building on scholarship that provides theological and ethical resources to support the 'greening' of religion, God and the Green Divide examines religious environmentalism as it actually happens in the daily lives of urban Americans. Baugh demonstrates how complex dynamics related to race, ethnicity, and class factor into decisions to 'go green.' By carefully examining negotiations of racial and ethnic identities as central to the history of religious environmentalism, this work complicates assumptions that religious environmentalism is a direct expression of theology, ethics, or religious beliefs"--Provided by publisher